2023
DOI: 10.1111/opo.13201
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intensity, spectral purity and duty cycle on red light‐induced hyperopia in tree shrews

Abstract: IntroductionThere have recently been several clinical studies suggesting that brief periods of exposure to red light (repeated low‐level red light, ‘RLRL’) may produce a dramatic anti‐myopia effect, calling for further investigations into its therapeutic parameters. Unfortunately, many experimental species used in refractive studies develop myopia in response to this wavelength. Tree shrews are the only animal model other than rhesus monkeys that consistently exhibit hyperopic responses to ambient red light. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…We note that we have previously shown that ambient narrow-band red light induces hyperopia in tree shrews, but even small amounts of added white (including blue) light greatly reduce this effect. 49 However, the chromatic simulations of myopic blur used here operate in broad-spectrum light. We hypothesize that, at least for this species, the red light by itself is interpreted as zero blue (short-wavelength) spatial contrast, similar to the flat blue pattern used here.…”
Section: Discussionmentioning
confidence: 99%
“…We note that we have previously shown that ambient narrow-band red light induces hyperopia in tree shrews, but even small amounts of added white (including blue) light greatly reduce this effect. 49 However, the chromatic simulations of myopic blur used here operate in broad-spectrum light. We hypothesize that, at least for this species, the red light by itself is interpreted as zero blue (short-wavelength) spatial contrast, similar to the flat blue pattern used here.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies in tree shrews, the dose-response effect was not obvious if the lighting was within 50 ~ 600 lux 23 . Likewise, we recorded no signi cant difference of CARE between the group of 0.37mW and the group of 1.20mW at any follow-up timeline.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the myopia control effect of the ambient narrowband red light in animals and low-level red-light therapy in humans could be mediated by differences in treatment duration or other light characteristics between these two lighting environments, for example, illumination (diffuse ambient red in the tree shrew and monkey experiments vs. potentially highly localized retinal intensities in low-level red light) or phase (diffuse vs. coherent). 75 Another possibility is that the myopia control efficacy of low-level red-light therapy in children is occurring via a different mechanism. It has been proposed that the effect of intense red light could instead be due to direct stimulation of mitochondria, which have components with an absorbance peak around 650 nm.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Regardless, given the similarity in the peak sensitivity, bandwidth, and spectral purity of the light, 75 the myopia control effect observed with low-level red-light therapy could be mediated via the same mechanism responsible for the long-wavelength light-induced hyperopia in tree shrews and monkeys. Specifically, the emmetropization mechanism could be using the long-wavelength image contrast as a cue that the eye is too long and generating STOP signals that slow eye growth 47,76 .…”
Section: Background: the Value Of Lightmentioning
confidence: 99%
See 1 more Smart Citation